2022
DOI: 10.3390/met12122038
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of In Situ Ti-6Al-4V/TiB Composites by the Hot-Pressing Method using Recycled Metal Chips

Abstract: In this study, a Ti-6Al-4V matrix composite reinforced with in situ synthesized TiB whiskers has been successfully produced from wasted chips by a cost-effective powder metallurgy route combining rapid heating and hot pressing. The effect of boron powder addition (1 vol.%, 3 vol.%, 5 vol.%, and 7 vol.%) on phase constituents, microstructures, and mechanical properties of the fabricated composites was investigated. Additionally, the effect of two different post-heat treatments on the 3 vol.% boron-containing co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
2
2
0
Order By: Relevance
“…Due to a high fraction of borides, an increase in B content to 1% increases room temperature strength but weakens superplastic properties and decreases ductility at both elevated and room temperatures. The same influence of boron on the room temperature properties was observed for Ti-6Al-4V alloy [58]. Authors of [15,59] observed an increased strength but decreased ductility and fracture toughness for the alloys with 0.4-2%B.…”
Section: Discussionsupporting
confidence: 61%
“…Due to a high fraction of borides, an increase in B content to 1% increases room temperature strength but weakens superplastic properties and decreases ductility at both elevated and room temperatures. The same influence of boron on the room temperature properties was observed for Ti-6Al-4V alloy [58]. Authors of [15,59] observed an increased strength but decreased ductility and fracture toughness for the alloys with 0.4-2%B.…”
Section: Discussionsupporting
confidence: 61%
“…Due to a high fraction of borides, an increase in B content to 1% increased room temperature strength but weakens superplastic properties and decreased ductility at both elevated and room temperatures. The same influence of boron on the room temperature properties was observed for Ti-6Al-4V alloy [ 53 ]. The authors of [ 15 , 54 ] observed an increased strength but decreased ductility and fracture toughness for the alloys with 0.4–2% B.…”
Section: Discussionsupporting
confidence: 57%
“…The rationale behind solid state recycling technique is based on the severe plastic deformation, introducing large shear deformation to enhance physical and metallurgical bonding. To date, an increasing number of solid-state recycling processes have been reported including ball milling, sintering [ 7 ], hot pressing [ 8 , 9 , 10 ], spark plasma sintering [ 11 ], hot extrusion [ 3 , 5 , 6 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ], equal channel angular pressing [ 25 , 26 , 27 , 28 , 29 ], cycling extrusion compression [ 30 , 31 ], friction stir extrusion [ 32 , 33 ], high-pressure torsion [ 34 ], and screw extrusion [ 35 ].…”
Section: Introductionmentioning
confidence: 99%